WHAT DOES IT MEAN “TO BE A GOOD NURSE”? PERCEPTIONS OF NURSING STUDENTS - Zydziunaite, Vilma; Bagdonaite-Stelmokiene, Ramune (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
“To be a good nurse” is a complex phenomenon. It is the essential goal in nursing training, education and practice, and can be experienced through work practice. However, “to be a good nurse” is taken for granted and is rarely studied, mostly with the focus on personal features and in relation to good nursing and quality of nursing. The aim was to reveal nursing students’ work experience-based perceptions of the personal meaning of “to be a good nurse”. Sample. Research participants comprised 110 final year nursing students. Methods. For data collection were used unstructured individual narrative-based written reflections and the data was analyzed by applying the inductive manifest qualitative content analysis. Results. For nursing students “to be a good nurse” means courage, professionalism, loyalty, humanity, solidarity and caring. It is an individually experienced phenomenon, meaningful for nursing students when they collaborate with nurse practitioners, learn through cooperation and observation, and have the opportunity to act autonomously by taking responsibility for their own actions. Conclusion. “To be a good nurse” is a part of who the student is and the values that s/he holds dear to her/him.